The development of the concept of international river in public international Law، - ‪Sharee Nanakaly; Mandan mohammed (الرافدین للحقوق)
Abstract:There is no doubt That any developments in the scientific and technological field lead to the development of the concept of some other legal terms, whether in national or international laws; The idea of the international river is a purely legal idea. Therefore, the contemporary trend of the concept of the international river has undergone fundamental changes in it by the International Law Commission of the United Nations, as It tends to abandon the traditional idea of the international river and replace it with the idea of the international drainage basin or the international water network as a natural resource. Common, so we will try in this research to explain the contemporary concept of the international river in light of the technological and scientific development in accordance with contemporary international legal rules and jurisprudential opinions on the subject of the research.